2022
DOI: 10.1111/odi.14253
|View full text |Cite
|
Sign up to set email alerts
|

Family history of cancer is associated with poorer prognosis in oral squamous cell carcinoma

Abstract: Objective The purpose of this study was to investigate the prognostic value of the family history of cancer (FHC) in predicting survival and clinicopathological features in oral squamous cell carcinoma (OSCC) patients. Materials and Methods This single‐institution study utilized data from 610 patients undergoing surgery from 2014 to 2020 that was prospectively collected and cataloged for research purposes. All patients underwent standard surgery with/without radiotherapy or chemoradiotherapy. We statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Cancer has the potential to make middle and low economic families become poorer. [7][8][9] According to the Jamkesmas (Health Insurance for the Poor) report, it was shown that in 2012 cancer treatment ranked second after hemodialysis, reaching 144.7 billion rupiahs. 10 Although Breast Cancer and Cervical Cancer are the most common cancers in women today, early detection of both types of cancer can be done with inexpensive and simple or simple appropriate technology and improving the quality of treatment by early detection using the Clinical Breast Examine (CBE), better known as BSE for breast cancer, and IVA and Pap smear methods for cervical cancer will accelerate the handling of these two types of cancer, so that the prognosis will be better and the cost of treatment services can also be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer has the potential to make middle and low economic families become poorer. [7][8][9] According to the Jamkesmas (Health Insurance for the Poor) report, it was shown that in 2012 cancer treatment ranked second after hemodialysis, reaching 144.7 billion rupiahs. 10 Although Breast Cancer and Cervical Cancer are the most common cancers in women today, early detection of both types of cancer can be done with inexpensive and simple or simple appropriate technology and improving the quality of treatment by early detection using the Clinical Breast Examine (CBE), better known as BSE for breast cancer, and IVA and Pap smear methods for cervical cancer will accelerate the handling of these two types of cancer, so that the prognosis will be better and the cost of treatment services can also be reduced.…”
Section: Introductionmentioning
confidence: 99%